STUDENTS’ RESPONSE TO SIMPLE ENGLISH INSTRUCTIONS USING TOTAL PHYSICAL RESPONSE (TPR) METHOD IN EFL CLASSROOM - Luruk, Yulita; Kamlasi, Imanuel; Lasi, Febronia (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2021)
The objective of this study are to what extent do the students face find difficulty to simple English Instruction in using Total Physical Response (TPR) Method and To what level is students’ mastery in using Total Physical Response (TPR) categorized? The method that used in this study is descriptive qualitative method. While to get the data needed the writer used Oral test with the topic classroom interaction and the research was observed and take the video. To analyss the data the writer can observed the students, who students can response and difficult to response on TPR and do the observed the researcher was categorized students into five (5) levels, such as: very good, good, enough, bad, and very bad. Based on research result the The extent do the students’ face find difficulty to simple english instruction using total physical response (TPR) is have 1 number it is number 10 ( take your bag please). And To what level is the student mastery in using Total Physical Response it offered in table 3, shows that there are have 13 students’ whose mastery is categorized to level very good, 2 students categirized to level good, and just 1 student is categorized to level Bad.